Novel 6p21.3 Risk Haplotype Predisposes to Acute Coronary Syndrome. (February 2016) - Sinisalo, Juha; Vlachopoulou, Efthymia; Marchesani, Marja; Nokelainen, Johanna; Mäyränpää, Mikko I.; Lappalainen, Jani; Paakkanen, Riitta; Wennerström, Annika; Salli, Krista; Niemi, Heikki J.; Männistö, Satu; Salo, Perttu; et al.
Abstract : Background—: The HLA-DRB1*01 allele of the human leukocyte antigen has been associated with acute coronary syndrome. Genome-wide association studies have revealed associations with human leukocyte antigen and non–human leukocyte antigen genes of 3 major histocompatibility complex gene classes but not at allelic level. Methods and Results—: We conducted a large-scale genetic analysis on a case–control cohort comprising 5376 acute coronary syndrome cases and 4852 unrelated controls from 4 populations of 2 European countries. We analyzed the risk candidate allele of HLA-DRB1*01 by genomic real-time polymerase chain reaction together with high-density single nucleotide polymorphisms of the major histocompatibility complex to precisely identify risk loci for acute coronary syndrome with effective clinical implications. We found a risk haplotype for the disease containing single nucleotide polymorphisms from BTNL2 and HLA-DRA genes and the HLA-DRB1*01 allele. The association of the haplotype appeared in 3 of the 4 populations, and the direction of the effect was consistent in the fourth. Coronary samples from subjects homozygous for the disease-associated haplotype showed higher BTNL2 mRNA levels ( r =0.760; P <0.00001).We localized, with immunofluorescence staining, BTNL2 in CD68-positive macrophages of the coronary artery plaques. In homozygous cases, BTNL2 blocking, in T-cell stimulation assays, enhanced CD4 + FOXP3 + regulatory T cell proliferation significantly (blocking versus nonblocking; P <0.05). Conclusions—: In cases with the risk haplotype for acute coronary syndrome, these results suggest involvement of enhanced immune reactions. BTNL2 may have an inhibitory effect on FOXP3 + T cell proliferation, especially in patients homozygous for the risk alleles. Clinical Trial Registration—: https://www.clinicaltrials.gov ; Unique Identifier: NCT00417534. Abstract : Supplemental Digital Content is available in the text.